Poor Self-Rated Oral Health Status and Associated Factors Amongst Adults in Algeria - Supa Pengpid; Karl Peltzer (Elsevier, 2023)
Background: Understanding the proportion and correlates of self-rated oral health (SROH) can assist in prioritising interventions. The aim of this study was to assess the prevalence of poor SROH and associated factors in a national community survey amongst adults in Algeria. Methods: This World Health Organisation (WHO) STEPS cross-sectional survey in Algeria in 2016 and 2017 included 6989 people (18-69 years; median age, 37 years) selected by multistage cluster sampling. The assessment included questionnaire information, physical measures, and biochemistry tests. The measures included questions on SROH, oral conditions, oral health behaviour, general health behaviour, and measures of health status. Results: The sample included 6989 people aged 18 to 69 years. Of the total sample, 17.1% had removable dentures, 35.5% had 0 to 19 natural teeth, 43.9% had dental pain in the past year, 40.5% had impaired oral health-related quality of life (OHRQoL), 26.9% cleaned their teeth 2 times/d or more, 79.6% used toothpaste, and 41.2% had visited a dentist in the past year. The prevalence of poor SROH was 37.3%. In the final logistic regression model, older age (45-69 years) (adjusted odds ratio [AOR], 1.34; 95% confidence interval [CI], 1.09-1.65), having removable dentures (AOR, 1.46; 95% CI, 1.14-1.87), dental pain (AOR, 2.16; 95% CI, 1.82-2.57), impaired OHRQoL (AOR, 2.69; 95% CI, 2.26-3.20), current smokeless tobacco use (AOR, 1.45; 95% CI, 1.12-1.89), and inadequate fruit and vegetable intake (AOR, 2.69; 95% CI, 2.26-3.20) increased the odds of poor SROH. Men (AOR, 0.76; 95% CI, 0.65-0.90), having 20 or more teeth (AOR, 0.35; 95% CI, 0.28-0.42), twice or more a day teeth cleaning (AOR, 0.72; 95% CI, 0.60-0.86), and using toothpaste (AOR, 0.67; 95% CI, 0.55-0.82) were protective against poor SROH. Conclusions: Adults in Algeria reported a high prevalence of poor SROH, and several associated factors (sociodemographic, oral conditions, oral and general health-compromising behaviour) were found that can guide in oral health promotion strategies in Algeria.